Internal stress and defect-related free volume in submicrocrystalline Ni studied by neutron diffraction and difference dilatometry. (2nd November 2017) - Kotzurek, J. A.; Hofmann, M.; Simic, S.; Pölt, P.; Hohenwarter, A.; Pippan, R.; Sprengel, W.; Würschum, R.
Abstract: A combined study of neutron diffraction and difference dilatometry on submicrocrystalline Ni prepared by high pressure torsion aims at studying the anisotropic behaviour during dilatometry and its relation to internal stress and structural anisotropy. Macroscopic stresses were undetectable in the dilatometer samples. Along with specific tests such as post cold-rolling, this shows that an observed anisotropic length change upon annealing is not caused by internal stress, but can be explained by the inherent microstructure, i.e. the anisotropic annealing of relaxed vacancies at grain boundaries of shape-anisotropic crystallites.